Pembangunan Pariwisata Dan Implikasinya Pada Pola Penguasaan Tanah Dalam Masyarakat Di Kawasan Bisnis Pariwisata - Sahnan - (Fakultas Hukum Universitas Mataram, 2011)
Many states in the world begin to develop the tourism business, because in this sector is not susceptible on economic fluctuation. The development of tourism business is seductive enough, because it can increase the state devise such as Indonesia, the devise income in the tourism sector is number 2 after petroleum (oil and natural gas). However in empirical level, the implementation of development in tourism sector is still not running such as expected. It is seen that in the development of tourism sector not to be equilibrated with the empowerment of society so that, it cause the society become empathic. And also the applied regulations are still overlapping, complicated bureaucracy, and still not serious the investors to implement the effort in tourism sectors. The development of tourism that is conducted by government exactly more orientate to increase the economic growth and more support the capital owners than society interest. Actually, the society has owned the land hereditarily long time ago according to the customary law, but they are not recognized by government as the legal owner, because the ownership is not based on written evidence such as land certificate. And also several rights of land that have ever issued by government is declared not legal during the existence of rights annoy the tourism development implementation.